Risks of Adverse Perinatal Outcomes after Repeat Terminations of Pregnancy by their Methods: a Nationwide Register‐based Cohort Study in Finland 1996–2013. Issue 6 (16th August 2017) - KC, S.; Gissler, M.; Virtanen, S. M.; Klemetti, R.
Abstract: Background: Repeat terminations of pregnancy (TOPs) are associated with an increased risk of adverse outcomes in the subsequent birth. The perinatal outcomes after repeat TOPs by their methods have not yet been properly studied. This study aimed to examine perinatal outcomes in subsequent pregnancy among the women with a singleton birth and a history of TOPs. Methods: All the first‐time mothers ( n = 419 879) with a singleton birth during 1996–2013 in Finland were identified from the Medical Birth Register and linked to the Abortion Register. Adjusted multivariable logistic regression analysis was used to estimate risks of adverse perinatal outcomes. Results: The increased incidence of adverse perinatal outcomes was found with increasing number of surgical TOPs. After adjusting for confounders, the women with one surgical TOP had slightly increased but significant odds of 1.07 (95% CI 1.02, 1.13) for being small for gestational age compared with the women having no TOP. A significantly high risk for extremely preterm birth (OR 1.51, 95% CI 1.03, 2.23) was found among the women having had repeat surgical TOPs when compared to the women with no TOP. Non‐significant risks were found for adverse perinatal outcomes after women's repeat surgical TOPs than repeat medical TOPs. Conclusion: Information regarding the consequences of repeat induced TOPs will be significant in sexual health education as well as counselling women after first termination.